Electromyography analysis of different instep kicking angle between kicking and supporting leg in football: a scoping review - Rosdi, Muhammad Hafizuddin Ahmad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
From the nature of the football games, movement skill is being facilitated by football practice. To analyse muscle activity for a football player, the muscle activities are analysed using EMG analysis. Players are prone to have muscle injury when performing a kick in the game, however the research on kicking technique based on the specific muscle activation is still lacking. Information from this study can be used to understand more about muscle mechanisms during kicking at a different angle that will help players in injury prevention and improve kicking performance. Data sources were acquired electronically by searching through 4 databases. The study selection was conducted using the Meta-analyses (PRISMA) guideline. Afterwards, the titles and abstracts of retrieved articles were reviewed using the criteria specified to determine whether full texts were required for further analysis in the data extraction. From review results, during instep kicking, an increase in surface EMG was observed in the Adductor Magnus muscle, but not in the Adductor Longus, Vastus Lateralis, or Bicep Femoris muscles, as the ball speed increased. The surface EMG of both the AM and AL muscles in the supporting leg increased considerably with an increase in ball speed before ball impact. The results of this review also revealed that in both kicking activities, the hamstring muscles of the kicking leg exhibited a significant magnitude of EMG activities before and after the kicking foot made contact with the ball, indicating that the hamstring muscles were activated. In conclusion, all of the studies found major muscle group activity during football kicking. The exact technique of instep kicking is thought to be determined by the pattern of muscle activation, and the muscular power and force distribution between the supporting leg and the kicking leg which plays a significant part in predicting and avoiding lower extremity injuries in football.